Prenatal Yoga dan Hipertensi: Menggali Manfaat untuk Kehamilan dengan Hipertensi melalui Tinjauan Sistematis - Pratiwi, Rizqi Dian (Journal of Midwifery Science: Basic and Applied Research, 2024)
Pregnancy with hypertension is one of the main factors causing maternal and fetal morbidity and mortality, so it must be managed holistically. Prenatal yoga is a therapy that involves the physical and psychological aspects of pregnant women.  The aim of this study is to determine the effect of prenatal yoga on pregnant women with hypertension. The research design was a literature review with an electronic literature search on PubMed, Google Scholar, and Science Direct from January 2014 to December 2024 and 6 primary studies were obtained. The results of the analysis show that prenatal yoga in pregnant women with hypertension can reduce systolic and diastolic blood pressure, increase maternal comfort during labor, reduce the duration of the first stage of labor, reduce the development of hypertension, improve fetomaternal outcomes, increase vascular endothelial function, increase heart rate variability (HRV), baroreflex sensitivity (BRS), and reduce inflammation. No negative effects were found in the 6 studies that were analyzed. Prenatal yoga can be recommended as an alternative for complementary therapy for pregnant women with hypertension.